The Iconography of the Painting Bugis Wedding Tradition by Andy Adryan Mallaena - thoriq bidar dardiri (TEXTURE Art and Culture Journal, 2025)
This research talked about “Bugis Wedding Tradition” by Andy Adryan Mallaena, analyzed through a qualitative approach using Erwin Panofsky’s theory of iconography. The aim of this study is to identify the artistic motifs, themes, concepts, and symbolic values present in the artwork. The results of this research are: a pre-iconographic description that provides an initial textual response, revealing two grasshopper-like figures depicted in a traditional Bugis wedding procession. The iconographic analysis explores the theme and concept of the uang panai social phenomenon, which has shifted in meaning from a sacred tradition to a transactional practice. The iconological interpretation addresses the symbolic values conveyed in the painting. Through the painter's psychological tendencies, inner turmoil, and his socio-cultural background, the painting emerges as a symbolic crystallization of the contradiction between loyalty to cultural roots and the ever-evolving social reality.